2004
DOI: 10.1542/peds.113.4.e313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Anaphylaxis in Children With Cold Urticaria

Abstract: ABSTRACT. Objective. To characterize the features of cold urticaria in children, with particular focus on systemic reactions, because little pediatric data are available.Methodology. Chart reviews of 30 children <18 years old who were evaluated in the past 3 years at the Children's Hospital Allergy Program (Boston, MA) and a private allergy practice. Demographic, diagnostic, and therapeutic data were collected. Telephone interviews of patients and/or their parents were performed to obtain follow-up data.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 19 publications
2
54
0
9
Order By: Relevance
“…Although clinical features of cold urticaria seem to be similar regardless of the age at symptom onset, in our series, patients with pediatric-onset ACU showed some differences; ACU was more difficultly induced through the ice cube test or the TempTest, and a complete resolution of symptoms was less likely to be achieved. These results are consistent with a previous pediatric study 3 in which complete symptom resolution was achieved in only 2 of 30 (7.4%) children with cold urticaria, and 41% of the patients had negative CSTs. Similarly, Santaolalla et al 11 noted a full recovery of symptoms in only 1 of 12 pediatric patients analyzed.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although clinical features of cold urticaria seem to be similar regardless of the age at symptom onset, in our series, patients with pediatric-onset ACU showed some differences; ACU was more difficultly induced through the ice cube test or the TempTest, and a complete resolution of symptoms was less likely to be achieved. These results are consistent with a previous pediatric study 3 in which complete symptom resolution was achieved in only 2 of 30 (7.4%) children with cold urticaria, and 41% of the patients had negative CSTs. Similarly, Santaolalla et al 11 noted a full recovery of symptoms in only 1 of 12 pediatric patients analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of atypical ACU in previous series varied between 8% and 49%. 3,9,10,12 Although the knowledge of this entity, especially regarding its natural history, is currently scarce, it has been postulated that these patients would need total body cooling to reflect cold urticaria symptoms. 1 A previous report also suggested a higher incidence of systemic reactions in these patients (10 patients with atypical ACU were analyzed, 6 presented with type II reactions and 2 with type III reactions).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cold urticaria can be classified according to its response to cold challenge test: if the ice cube test turns positive, it is primary or secondary, according to its aetiology; if the response is atypical (late or in a distant place from where stimulus was applied) or negative with suggestive clinical symptoms, it is atypical acquired urticaria 1,3,6 . Primary or idiopathic acquired urticaria is the most common form: Neittaanmäki 7 found a prevalence of 96 % in 220 patients studied with cold urticaria, Santaolalla et al 8 in a review of 12 paediatric cases found an infection cause in only one case and Alangari et al 9 , in a series of 30 children with cold urticaria didn't find any secondary cause.…”
Section: Discussionmentioning
confidence: 99%